Distribution of dragonfly populations at disturbed and undisturbed habitats in Negeri Sembilan / Amira Md. Zaliyati - Md. Zaliyati, Amira (Faculty Applied Science, 2014)
This study on distribution of dragonfly populations at disturbed and undisturbed habitats were conducted at UiTM Forest Reserve and Paddy Field of Kampung Lonek where UiTM Forest Reserve classified as undisturbed habitat while Paddy Field of Kampung Lonek as disturbed habitat. Objectives of this study were to determine the distribution of dragonfly within two different habitats in Negeri Sembilan and to determine the species diversity of dragonfly within two different habitats in Negeri Sembilan. It was carried out at the end of August until the end of October 2013 with six sampling occasions where three sampling were conducted at UiTM Forest Reserve and another three sampling were conducted at Paddy Field of Kampung Lonek. Throughout this study, a total of 164 individual dragonflies represent 14 species from two families were collected. From the 14 species of dragonfly, 11 species with 62 individuals of dragonflies collected from UiTM Forest Reserve while 9 species with 102 individuals of dragonflies collected from Paddy Field of Kampung Lonek. Family Libellulidae was the dominant family that indicate 99 % of total collected followed by one percent of total collected by Family Gomphidae. The higher total number of dragonfly individuals was shown by Potamarcha congener with 52 individuals that indicate 32 % of total collected while the least number of individual shown by the species of Orthetrum chrysis, Tholymis tillarga and Ictinogomphus decoratus with one individual that indicate only one percent, respectively. Habitat give influence to the species of dragonfly as shown by Chi-Square value, X2 = 120.164. Thus, there was high species diversity, high species richness and high species evenness of dragonfly at UiTM Forest Reserve compared to Paddy Field of Kampung Lonek.